Critical factors of e-government in the last 20 years: a study through content analysis and keyword co-occurrence (Research, Society and Development, 2022)
About 20 years have passed since the implementation of e-government as a tool that offers services and helps citizens, until today. Thus, the objective of this study is to raise the most frequent critical factors to understand the focus of study of researchers over the years on the subject, helping to identify trends. Therefore, a content analysis study was carried out on a sample of articles and a bibliometric analysis of the co-occurrence of the keywords from 2001 to 2022. As a result, the most relevant critical factors are the Digital Divide, the Implementation of Services that depend on infrastructure, studies on E-services, followed by Safety and Quality requirements, and finally, research on the Adoption/acceptance and trust of this user concerning the electronic system.